New scoring system to reduce unfairness in men`s doubles - Pollard, G.; Noble, K.; Pollard, G. (Journal of Sports Analytics, 2023)
Tennis uses essentially the same scoring system in doubles as in singles. In this paper it is shown that the scoring system commonly used in men`s doubles has the potential to be unfair. Aspects of this potential unfairness are identified and methods for reducing it are outlined. The statistical characteristics of the present scoring system are compared with those of a proposed new system.